A prospective study of the factors affecting anticoagulant control in a hospital out-patient clinic. Issue 638 (December 1978) - Shepherd, A. M. M.; Christopher, L. J.; Stevenson, I. H.; Henney, C. R.; Brown, Y.
Abstract : Anticoagulant control (as indicated by the percentage of Thrombotest values outside a defined range) was determined in out-patients attending a hospital anticoagulant clinic and the influence of patients' age and sex, indication for anticoagulation, concurrent drug therapy and duration of anticoagulant treatment studied. Of these factors, duration of treatment was most important, control being particularly poor in the first 6 months (40% of Thrombotest values outside the 5-15% range, compared with 17% in patients treated with anticoagulants for more than 2 years). Control was also influenced by patients' age and the data supported previous evidence of an increased sensitivity to anticoagulants in the elderly.